Theoretical investigation of the OH-initiated atmospheric decomposition of chlorpyrifos and chlorpyrifos-methyl - Mateus Macedo Quintano (2020)
This work aimed for an elucidation of the mechanism of tropospheric decomposition of the organophosphorus pesticides chlorpyrifos and chlorpyrifos-methyl using calculations based on the density functional theory (DFT) with dispersion correction and on the transition state theory (TST). We proposed a novel alternative route for the unimolecular decomposition of OH-initiated intermediates produced by OH-addition to the thiophosphoryl bond. Within such route, 3,5,6-trichloro-2-pyridinol (TCP), which is one of the main carbon-containing breakdown products, is obtained in a single step. Besides, we showed that TCP exists according to a ketone-enol equilibrium in the atmosphere at the ambient conditions. Also, we were able to show that the OH-addition occurs preferentially at the phosphorus atom. The P-bonded adducts can either follow a unimolecular decomposition pathway or react competitively with molecular oxygen, which accounts for the formation of the corresponding oxone.